2008
DOI: 10.1021/ic702390q
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Tetrabromocatecholatomanganese(III) Complexes with Dioxygen

Abstract: New five- and six-coordinate complexes containing the [Mn(III)(Br4cat)2](-) core (Br4cat(2-) = tetrabromo-1,2-catecholate) have been prepared. Homoleptic [Mn(III)(Br4cat)3](3-) reacts rapidly with O2 to produce tetrabromo-1,2-benzoquinone (Br4bq). The [Mn(III)(Br4cat)2](-) fragment is a robust catalytic platform for the aerobic conversion of catechols to quinones. The oxidase activity apparently derives from the coupling of metal- and ligand-centered redox events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…This is also supported by our earlier work on Mn III acetate [32], where we could find binding of three DTBC. Earlier works with substituted catechols as ligand using Mn, Co, Fe and Cu as metal ions also support the formation of similar species [152][153][154][155][207][208][209][210]. It seems that Mn is the best choice as the metal and it needs to be more explored with suitable ligands for tuning the activity.…”
Section: Discussionmentioning
confidence: 93%
“…This is also supported by our earlier work on Mn III acetate [32], where we could find binding of three DTBC. Earlier works with substituted catechols as ligand using Mn, Co, Fe and Cu as metal ions also support the formation of similar species [152][153][154][155][207][208][209][210]. It seems that Mn is the best choice as the metal and it needs to be more explored with suitable ligands for tuning the activity.…”
Section: Discussionmentioning
confidence: 93%
“…[75][76][77][78][79] Utilization of redox noninnocence for reactivity purposes currently occupies many researchers. [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] One fundamental question is does the location of spin density within a molecule influence its bond making/breaking chemical reactivity?…”
Section: Discussionmentioning
confidence: 99%
“…The singlet state Co radical 79 Co did not show any ligand-centered In a different instance of O 2 reactivity, Soper et al 146 have shown that homoleptic MnBr 4 (catechol) 3 undergo oxidation of the ligand when exposed to O 2 . The O 2 molecule is reduced by 2e À and the ligand lost is the o-quinone oxidized form of the ligand.…”
Section: N Oxygen Activationmentioning
confidence: 93%